A Descent Conjugate Gradient Method For Large Scale Unconstrained Optimization Problems With Application - Ahmad Alhawarat; Sultanah Masmali; Ibrahim M. Sulaiman; Issam A. R. Moghrabi; Norazura Ahmad; Shahrina Ismail (American Scientific Publishing Group (ASPG), 2026)
Indexed by Scopus